Investigating the Effect of Gallic Acid on Serum BDNF Levels in Patients with Major Depression - Seyed Hamzeh Hosseini; Hossein Khadem haghighian; Zahra Yari Sarokolae; Atefeh Arab firozjae; Sara Bayat; Reza Eshaghi Gorji; Majid Saeedi; Gholamreza Houshmand (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Changes in Brain-Derived Neurotrophic Factor (BDNF) levels are associated with psychiatric disorders, including depression. Research has demonstrated that patients suffering from depression exhibit reduced BDNF levels, and antidepressant treatments have been shown to increase these levels. Gallic acid, a natural compound known for its antioxidant and neurotrophic properties, shows significant potential for enhancing BDNF levels and alleviating depressive symptoms. This study aims to investigate the effect of gallic acid supplementation on serum BDNF levels in patients diagnosed with depression. Materials and methods: This study was conducted using serum samples obtained from our previous research involving 30 patients diagnosed with major depressive disorder who visited Shahid Zareh Hospital in Sari. The patients were randomly divided into two groups: an intervention group and a placebo group. Individuals in the intervention group received 200 mg of gallic acid daily in capsule form. Blood samples (10 cc) were collected from each participant at both the start and the end of the study. Following serum separation, the levels of BDNF in the plasma samples were measured using a specific ELISA kit. Results: After the intervention, the findings showed a significant difference between the plasma BDNF levels of the research groups. The plasma BDNF levels in the intervention group increased significantly compared to the placebo group. Conclusion: According to the results, gallic acid supplementation increases the level of BDNF, and this supplement may be used in conjunction with existing antidepressants to reduce the side effects of current drugs.